Breeding activities in Africa - Davis, J. (International Center for Tropical Agriculture, 1989)
A summary on bean improvement activities carried out by CIAT in the Great Lakes Region is presented. Collaboration in bean breeding among Rwanda, Burundi, and Zaire has resulted in an integrated scheme of var. evaluation. The nucleus of this scheme is the PRELAAC (Pepiniere Regionale pour l`Evaluation des Lignees Avancees de l`Afrique Centrale) nursery, which brings together the var. entering the comparative yield trials in each country. The purpose of the nursery is to evaluate for resistance to diseases or pests, in a range of suitable locations. In the PRELAAC for 1988, bush var. A 231 showed combined resistance to BCMV, anthracnose, halo blight, and Ascochyta. XAN 68 was resistant to Ascochyta, halo blight, and angular leaf spot. Excellent resistance to anthracnose was found in AND 303 and RWR 45. Among climbers, ZAV 83052 was resistant to BCMV, anthracnose, and halo blight. Resistance to BCMV and halo blight was found in ACV 83031 and promising resistance to anthracnose in AFR 229 and VAMY-127-310-S5. In the Essais Regionaux des Grands Lacs for 1988, the best bush var. in terms of yield were PVA 15, PVA 1432, PVA 1438, and AND 303. The best climbers were AFR 13 and ZAV 83052. These var. will be incorporated to the African Bean Yield and Adaptation Nursery as candidates for var. release. (CIAT)